ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP STRUKTUR MODAL (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018 – 2019) - Putri Dzakiya; Abdul Rohman (Diponegoro Journal of Accounting, 2022)
This research was conducted to analyze the effect of corporate governance mechanisms on capital structure. The independent variable of this research is the corporate governance mechanism which consists of size of the board of commissioners, size of the directors, size of audit committee, concentration of ownership, institutional ownership, and managerial ownership. The dependent variable of this research is capital structure. The population of this research are manufacturing companies listed on the Indonesia Stock Exchange in 2018 – 2019. This research uses purposive sampling method by taking samples based on certain criteria. With the existing criteria, 178 eligible samples are used. This research was conducted using multiple linear regression analysis method. The results of this research were found that institutional ownership has a significant positive effect on capital structure, while the size of the board of directors and managerial ownership has a significant negative effect on capital structure. This research also finds that the size of the board of commissioners, the size of the audit committee, and concentration of ownership has no significant effect on capital structure.